Identity‐based motivation and consumer behavior - Oyserman, Daphna (Journal of Consumer Psychology, 2009)
Abstract Choices are often identity‐based yet the identity‐to‐choice link is not necessarily obvious for reasons articulated by the identity‐based motivation model (Oyserman, D. (2009). Identity‐based motivation: Implication for action‐readiness, procedural readiness and consumer behavior. Journal of Consumer Psychology). Specifically, which identities are salient and what identities mean in the moment are highly dependent on situational cues. Though they feel stable, identities are dynamically shaped by situational affordances and constraints and this shaping process can occur without conscious awareness. This implies that product use, including use of utilitarian products, can become identity‐based, as can both self‐constructive and self‐destructive choices. Over time, broader identities are more likely to be cued than more narrow ones, though any identity can be cued in the right circumstances. The commentaries apply the model to culture‐contingent effects of power (Shavitt, S., Torelli, C. & Wong, J. (2009). Identity‐based motivation: Constraints and opportunities in consumer research. Journal of Consumer Psychology), charitable giving (Aaker, J. & Akutsu, S. (2009). Why do people give? The role of identity in giving. Journal of Consumer Psychology), and the consequences of salient identities for self‐constructive vs. self‐destructive choices (Kirmani, A. (2009). The self and the brand. Journal of Consumer Psychology) and this commentary addresses some of the questions they raise.